Preparation method of double-layer core-shell structure PS / TiO2 / CeO2 nano composite abrasive
By using PS/TiO2/CeO2 nanocomposite abrasives with a double-layer core-shell structure and utilizing the synergistic effect of polystyrene microspheres, titanium oxide and cerium oxide, the problem of damage and surface quality of KDP crystals during processing is solved, and high efficiency is achieved. Improved polishing effect and surface quality.
Patent Information
- Application Number
- CN202411577847.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-11-06
AI Technical Summary
Potassium dihydrogen phosphate (KDP) crystals are prone to damage to edge collapse and small wrigor during processing, and their surface quality has a significant impact on optical performance. The existing single abrasives cannot meet the requirements of high polishing quality.
The preparation method of double-layer core-shell structure PS/TiO2/CeO2 nanocomposite abrasives is used. Polystyrene microspheres are used as the core, titanium oxide is used as the middle layer, and cerium oxide is used as the outer layer to form a composite abrasive. The combination of titanium oxide and cerium oxide is used. Synergistic effect improves polishing effect.
This composite abrasive can effectively reduce mechanical damage to the surface of the KDP crystal surface during polishing, improve the quality of polishing surface, while maintaining high material removal rate, significantly improved the polishing effect.
Smart Images

Figure CN119351056A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nano composite materials, and in particular relates to a method for preparing a double-layer core-shell structured PS / TiO2 / CeO2 nano composite abrasive. Background Art
[0002] Potassium dihydrogen phosphate (KDP) crystal is a nonlinear optical crystal with excellent performance. It is widely used in inertial confinement nuclear fusion devices, high-power laser weapons, tunable acousto-optic filters, electro-optic switches and other fields. Due to its soft and brittle, easy to deliquesce, anisotropic and other characteristics, it is easy to cause damage such as edge collapse and small waviness. It is one of the most difficult materials to process. Its surface quality has a great influence on its optical properties, and the polishing method and abrasive type will directly affect the polishing surface quality.
[0003] Chemical mechanical polishing (CMP) technology is a polishing process that achieves a globally flat surface through the dual coupling effects of chemical corrosion of chemical reagents in the polishing solution and mechanical grinding. It is currently a technology that is widely used in the field of ultra-precision machining. Abrasive is an important component of polishing liquid. The material, morphology, particle size, particle size distribution and other properties of the abrasive itself are the main factors that determine the polishing effect. Since KDP crystal has high requirements for polishing quality, the performance of existing single abrasive cannot meet the requirements. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a double-layer core-shell structure PS / TiO2 / CeO2 nanocomposite abrasive. The composite abrasive prepared by the method has a good polishing effect on KDP crystals.
[0005] To solve the above problems, the present invention adopts the following technical solutions:
[0006] The present invention provides a method for preparing a double-layer core-shell structure PS / TiO2 / CeO2 nanocomposite abrasive, comprising the following steps:
[0007] Step 1, preparing polystyrene (PS) microspheres: adding styrene and methacryloyloxyethyl trimethylammonium chloride to a polyvinyl pyrrolidone aqueous solution, heating to boiling, and then adding 2,2-azobis(2-methylpropylimidazole) dihydrochloride to react to obtain a polystyrene emulsion, and drying and grinding the emulsion to obtain PS microspheres.
[0008] Step 2, preparing PS / TiO2 composite microspheres: dispersing the PS microspheres prepared in step 1 into anhydrous ethanol to prepare a PS ethanol solution, and uniformly dispersing by ultrasonication; then adjusting the pH value of the mixed solution to 6-9 with ammonia water, and heating it; then adding an ethanol solution of an organic titanate to stir the reaction; after the reaction is completed, centrifuging the product, and repeatedly washing it with deionized water and anhydrous ethanol; then drying and grinding it to obtain PS / TiO2 composite microspheres.
[0009] Step 3, preparing PS / TiO2 / CeO2 composite abrasive: dispersing the PS / TiO2 composite microspheres prepared in step 2 into deionized water to prepare a PS / TiO2 aqueous solution, and uniformly dispersing it by ultrasonication; then adding soluble cerium salt and hexamethylenetetramine; stirring the reaction under heating conditions; after the reaction is completed, centrifuging the final product, and repeatedly washing it with deionized water and anhydrous ethanol; finally drying and grinding to obtain the PS / TiO2 / CeO2 composite abrasive.
[0010] Furthermore, in step 1, the concentration of the polyvinyl pyrrolidone aqueous solution is 0.5g / L~6g / L; the dosage relationship of styrene and polyvinyl pyrrolidone aqueous solution is 45g~150g:1L; the dosage relationship of methacryloyloxyethyl trimethyl ammonium chloride and polyvinyl pyrrolidone aqueous solution is 0.5g~5.5g:1L; the dosage relationship of 2,2-azobis(2-methylpropylimidamide) dihydrochloride and polyvinyl pyrrolidone aqueous solution is 0.5g~2.5g:1L; in step 1, a constant temperature oil bath is used for heating, the heating temperature is 100~110°C, and the reaction is carried out for 5~8h after adding 2,2-azobis(2-methylpropylimidamide) dihydrochloride.
[0011] Furthermore, in step 2, the organic titanate is any one of tetrabutyl titanate, isopropyl titanate, and titanium isopropoxide, or a combination thereof.
[0012] Furthermore, in step 2, the concentration of the PS ethanol solution is 5 g / L to 30 g / L, and the concentration of the organic titanate ethanol solution is 10 g / L to 100 g / L; in step 2, a constant temperature oil bath is used for heating, the heating temperature is 70 to 90° C., and the reaction time is 2 to 4 hours.
[0013] Furthermore, in step 3, the soluble cerium salt is any one of cerium nitrate, cerium sulfate, cerium chloride, or a combination thereof.
[0014] Furthermore, in step 3, the concentration of the PS / TiO2 aqueous solution is 2.5g / L~15g / L, the dosage of the soluble cerium salt and the PS / TiO2 aqueous solution is 20g-100g:1L; the molar ratio of the soluble cerium salt to hexamethylenetetramine is 1:5; in step 3, a constant temperature oil bath is used for heating, the heating temperature is 60~85°C, and the reaction time is 2~4h.
[0015] The beneficial effects of the present invention are as follows: the present invention provides a method for preparing a double-layer core-shell structured PS / TiO2 / CeO2 nanocomposite abrasive, wherein the core of the composite abrasive prepared by the method is a polystyrene microsphere, and the polystyrene microsphere is double-coated with titanium oxide as an intermediate layer and cerium oxide as an outer layer; the composite abrasive combines the advantages of organic polymers and metal oxides, and during the polishing process, the synergistic effect of titanium oxide and cerium oxide can improve the material removal rate; in addition, the composite abrasive has a core-shell structure that is soft inside and hard outside and can exert a special polishing effect; specifically, during the polishing process, the soft polystyrene core can buffer the polishing pressure borne by the KDP crystal, reduce excessive mechanical damage to the polishing surface caused by the coating layer, and thereby enable the polished surface to obtain better surface quality. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 Shown is a SEM image of the PS microspheres prepared in Example 1 of the present invention.
[0017] Figure 2 Shown are FTIR images of PS microspheres, PS / TiO2 composite microspheres and PS / TiO2 / CeO2 composite abrasives prepared in Example 1 of the present invention.
[0018] Figure 3 Shown is the XRD diagram of the PS / TiO2 composite microspheres and PS / TiO2 / CeO2 composite abrasives prepared in Example 1 of the present invention.
[0019] Figure 4 Shown are SEM images of PS microspheres prepared with three different DMC dosages of the present invention.
[0020] Figure 5 Shown are TEM images of PS / TiO2 / CeO2 composite abrasives prepared at three dosages of cerium nitrate according to the present invention.
[0021] Figure 6 Shown are AFM images of the PS / TiO2 / CeO2 composite abrasive prepared in Example 1 of the present invention and CeO2 and PS / CeO2 abrasives after polishing KDP crystals. DETAILED DESCRIPTION
[0022] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention will be further described in detail below in conjunction with specific embodiments. The following description is only used to illustrate the technical solution of the present invention but not to limit it. The experimental methods used in the embodiments are conventional methods unless otherwise specified. The materials, reagents, etc. used can be obtained from commercial channels unless otherwise specified.
[0023] Example 1
[0024] A method for preparing a double-layer core-shell structure PS / TiO2 / CeO2 nanocomposite abrasive comprises the following steps:
[0025] Step 1: Preparation of polystyrene (PS) microspheres:
[0026] Prepare a polyvinylpyrrolidone (PVP) aqueous solution with a concentration of 1.25 g / L, stir it evenly, pour it into a flask and place it in a constant temperature oil bath; add styrene and methacryloyloxyethyltrimethylammonium chloride (DMC); the dosage relationship of styrene to PVP aqueous solution is 90 g:1 L; the dosage relationship of DMC to PVP aqueous solution is 1.4 g:1 L; then start stirring and heat to 105°C; keep warm at 105°C for 5 minutes, then add 2,2-azobis(2-methylpropylimidamide) dihydrochloride (AIBA) and stir to react for 6 hours; the dosage relationship of AIBA to PVP aqueous solution is 1 g:1 L; the emulsion obtained by the reaction is placed in a 60-90°C drying oven for drying, and after drying, it is ground to obtain PS microspheres.
[0027] like Figure 1 The SEM image of PS microspheres prepared in Example 1 of the present invention is shown. Figure 1 It can be seen that the PS microspheres prepared in this example are spherical, without adhesion, agglomeration, and rupture, and have uniform particle size and good monodispersity. The average particle size of the PS microspheres is 131 nm.
[0028] Step 2: Preparation of PS / TiO2 composite microspheres:
[0029] The PS microspheres prepared in step 1 are dispersed in anhydrous ethanol to prepare a PS ethanol solution with a concentration of 16g / L, and ultrasonically dispersed uniformly; then the pH value of the mixed solution is adjusted to 7 with ammonia water and poured into a flask, and the flask is placed in an oil bath; stirring is started and the temperature is raised to 80°C; then 30g / L of tetrabutyl titanate ethanol solution is added dropwise into the flask and stirred for 3h. After the reaction is completed, centrifugation is performed and the mixture is repeatedly washed with deionized water and anhydrous ethanol; then, the mixture is dried in a drying oven at 60-90°C, and the PS / TiO2 composite microspheres are obtained by grinding after drying.
[0030] Step 3: Preparation of PS / TiO2 / CeO2 composite abrasive:
[0031] The PS / TiO2 composite microspheres prepared in step 2 are dispersed into a PS / TiO2 aqueous solution with a concentration of 5g / L in deionized water, and ultrasonically dispersed uniformly; then cerium nitrate and hexamethylenetetramine are added; wherein the dosage relationship of cerium nitrate and PS / TiO2 aqueous solution is 50g:1L; the molar ratio of cerium nitrate to hexamethylenetetramine is 1:5; after complete dissolution, pour into a flask, and place the flask in an oil bath; stir the reactants in the flask evenly and heat to 75°C, and continue the reaction for 3h. After the reaction is completed, the final product is centrifuged and repeatedly washed with deionized water and anhydrous ethanol; finally, it is dried in a drying oven at 60-90°C, and after drying, it is ground to obtain a PS / TiO2 / CeO2 composite abrasive.
[0032] like Figure 2 Shown are FTIR images of PS microspheres, PS / TiO2 composite microspheres and PS / TiO2 / CeO2 composite abrasives prepared in Example 1 of the present invention. Figure 3 Shown is the XRD diagram of the PS / TiO2 composite microspheres and PS / TiO2 / CeO2 composite abrasives prepared in Example 1 of the present invention.
[0033] from Figure 2 It can be seen from the FTIR curve of PS microspheres that at 1603.2 cm -1 、1494.6cm -1 and 1450cm -1 The characteristic peak at 1070.9cm is the stretching vibration peak of C=C on the benzene ring; -1 and 1026.4cm -1 The characteristic peak at 755.4cm is the in-plane bending vibration peak of the monosubstituted benzene ring CH; -1 and 697.9cm -1 The characteristic peaks at 3387cm are the out-of-plane bending vibration peaks of the monosubstituted benzene ring CH. These characteristic peaks indicate that styrene undergoes polymerization to form polystyrene. For PS / TiO2 composite microspheres, the peak at 3387cm -1 The broad characteristic peak near the surface of the microspheres is the stretching vibration band of the hydroxyl group -OH formed by the water binding. The infrared absorption peak of amorphous TiO2 is between 400 and 800 cm -1 From the figure, it can be clearly seen that at 540cm -1 There is an obvious characteristic peak at 1026.4cm, which is the characteristic peak of Ti-O-Ti, indicating that TiO2 exists on the surface of PS microspheres in the sample. -1 The characteristic peak at 699.3cm is the characteristic peak of Ce-O. -1 The characteristic peak at is the asymmetric stretching vibration peak of Ce-O-Ce metal oxide in the lattice, indicating the presence of CeO2 in the sample.
[0034] from Figure 3 It can be seen that the PS / TiO2 composite microspheres prepared in Example 1 of the present invention have only one obvious amorphous diffraction peak near 2θ=21°, and combined with the TEM image of the PS / TiO2 composite microspheres, it is shown that TiO2 exists in the composite microspheres in an amorphous structure. The PS / TiO2 / CeO2 composite abrasive exhibits characteristic diffraction peaks of CeO2 with a cubic fluorite structure at 2θ=28.7°, 33.2°, 47.5°, 56.4°, 59°, 69.5°, 76.6° and 78.8°, and a weak TiO2 amorphous diffraction peak appears near 2θ=21°, which indicates that the cerium oxide grain layer has completely coated the titanium oxide layer, and the PS / TiO2 / CeO2 composite abrasive forms a double-layer core-shell structure.
[0035] Example 2
[0036] A method for preparing a double-layer core-shell structure PS / TiO2 / CeO2 nanocomposite abrasive comprises the following steps:
[0037] Step 1: Preparation of polystyrene (PS) microspheres:
[0038] Prepare a polyvinylpyrrolidone (PVP) aqueous solution with a concentration of 0.5 g / L, stir it evenly, pour it into a flask and place it in a constant temperature oil bath; add styrene and methacryloyloxyethyltrimethylammonium chloride (DMC); the dosage relationship of styrene to PVP aqueous solution is 45 g:1L; the dosage relationship of DMC to PVP aqueous solution is 0.5 g:1L; then start stirring and heat to 100°C; keep warm at 100°C for 5 minutes, then add 2,2-azobis(2-methylpropylimidamide) dihydrochloride (AIBA) and stir to react for 5 hours; the dosage relationship of AIBA to PVP aqueous solution is 0.5 g:1L; the emulsion obtained by the reaction is placed in a drying oven at 60-90°C for drying, and after drying, it is ground to obtain PS microspheres.
[0039] Step 2: Preparation of PS / TiO2 composite microspheres:
[0040] The PS microspheres prepared in step 1 are dispersed in anhydrous ethanol to prepare a PS ethanol solution with a concentration of 5g / L, and ultrasonically dispersed uniformly; then the pH value of the mixed solution is adjusted to 6 with ammonia water and poured into a flask, and the flask is placed in an oil bath; stirring is started and the temperature is raised to 70°C; then 10g / L tetrabutyl titanate ethanol solution is added dropwise into the flask and stirred for 2h. After the reaction is completed, centrifugation is performed and the mixture is repeatedly washed with deionized water and anhydrous ethanol; then, the mixture is dried in a drying oven at 60-90°C, and the PS / TiO2 composite microspheres are obtained by grinding after drying.
[0041] Step 3: Preparation of PS / TiO2 / CeO2 composite abrasive:
[0042] The PS / TiO2 composite microspheres prepared in step 2 are dispersed into a PS / TiO2 aqueous solution with a concentration of 2.5g / L in deionized water, and ultrasonically dispersed uniformly; then cerium nitrate and hexamethylenetetramine are added; wherein the dosage relationship of cerium nitrate and PS / TiO2 aqueous solution is 20g:1L; the molar ratio of cerium nitrate to hexamethylenetetramine is 1:5; after complete dissolution, pour into a flask, and place the flask in an oil bath; stir the reactants in the flask evenly and heat to 60°C, and continue the reaction for 2h. After the reaction is completed, the final product is centrifuged and repeatedly washed with deionized water and anhydrous ethanol; finally, it is dried in a drying oven at 60-90°C, and after drying, it is ground to obtain a PS / TiO2 / CeO2 composite abrasive.
[0043] Example 3
[0044] A method for preparing a double-layer core-shell structure PS / TiO2 / CeO2 nanocomposite abrasive comprises the following steps:
[0045] Step 1: Preparation of polystyrene (PS) microspheres:
[0046] Prepare a polyvinylpyrrolidone (PVP) aqueous solution with a concentration of 6 g / L, stir it evenly, pour it into a flask and place it in a constant temperature oil bath; add styrene and methacryloyloxyethyltrimethylammonium chloride (DMC); the dosage relationship of styrene to PVP aqueous solution is 150 g:1L; the dosage relationship of DMC to PVP aqueous solution is 5.5 g:1L; then start stirring and heat to 110°C; keep warm at 110°C for 5 minutes, then add 2,2-azobis(2-methylpropylimidamide) dihydrochloride (AIBA) and stir to react for 8 hours; the dosage relationship of AIBA to PVP aqueous solution is 2.5 g:1L; the emulsion obtained by the reaction is placed in a 60-90°C drying oven for drying, and after drying, it is ground to obtain PS microspheres.
[0047] Step 2: Preparation of PS / TiO2 composite microspheres:
[0048] The PS microspheres prepared in step 1 are dispersed in anhydrous ethanol to prepare a PS ethanol solution with a concentration of 30g / L, and ultrasonically dispersed uniformly; then the pH value of the mixed solution is adjusted to 9 with ammonia water and poured into a flask, and the flask is placed in an oil bath; stirring is started and the temperature is raised to 90°C; then 100g / L of tetrabutyl titanate ethanol solution is added dropwise into the flask and stirred for 4h. After the reaction is completed, centrifugation is performed and the mixture is repeatedly washed with deionized water and anhydrous ethanol; then, the mixture is dried in a drying oven at 60-90°C, and the PS / TiO2 composite microspheres are obtained by grinding after drying.
[0049] Step 3: Preparation of PS / TiO2 / CeO2 composite abrasive:
[0050] The PS / TiO2 composite microspheres prepared in step 2 are dispersed into a PS / TiO2 aqueous solution with a concentration of 15g / L in deionized water, and ultrasonically dispersed uniformly; then cerium nitrate and hexamethylenetetramine are added; wherein the dosage relationship of cerium nitrate and PS / TiO2 aqueous solution is 100g:1L; the molar ratio of cerium nitrate to hexamethylenetetramine is 1:5; after complete dissolution, pour into a flask, and place the flask in an oil bath; stir the reactants in the flask evenly and heat to 85°C, and continue the reaction for 4h. After the reaction is completed, the final product is centrifuged and repeatedly washed with deionized water and anhydrous ethanol; finally, it is dried in a drying oven at 60-90°C, and after drying, it is ground to obtain a PS / TiO2 / CeO2 composite abrasive.
[0051] According to detection, the particle size of the polystyrene microspheres prepared by the method of the present invention is 100-200 nm; the thickness of the titanium oxide layer is 10-30 nm; and the thickness of the cerium oxide layer is 5-30 nm.
[0052] Comparative experiment 1
[0053] Based on Example 1, only the amount of DMC in step 1 was changed to study its effect on the material of the present invention. Specifically, DMC was not added in one of the preparation methods, and the amount of DMC and PVP aqueous solution was 4.2 g:1 L.
[0054] like Figure 4 The SEM images of PS microspheres prepared by three different DMC dosages of the present invention are shown. From left to right, the DMC dosage is no DMC, the dosage relationship of DMC and PVP aqueous solution is 1.4g:1L, and the dosage relationship of DMC and PVP aqueous solution is 4.2g:1L.
[0055] from Figure 4 As can be seen in (a), when DMC is not added, the particle size of the prepared PS microspheres is very uneven and the surface morphology is rough. After adding DMC, the particle size of the PS microspheres is significantly reduced, and the particle size distribution becomes uniform (e.g. Figure 4 (b)). When the amount of DMC increases to a certain value, the particle size of PS microspheres will decrease (as shown in Figure 4 (c)). This is because the addition of DMC accelerates the nucleation rate of PS and increases the number of nuclei, which leads to a decrease in the average particle size.
[0056] Comparative experiment 2
[0057] On the basis of Example 1, only the concentration of tetrabutyl titanate ethanol solution in step 2 was changed to study its effect on the material of the present invention. Specifically, the concentrations of tetrabutyl titanate ethanol solution were 15, 20, 25, 30, 35, and 40 g / L, respectively; the experiment obtained a series of PS / TiO2 composite microspheres with different TiO2 layer thicknesses, as shown in Table 1 below.
[0058] Table 1. Statistical table of the effects of different concentrations of tetrabutyl titanate ethanol (TBOT) solution on the thickness of the TiO2 layer in PS / TiO2 composite microspheres.
[0059] From the data in Table 1, we can see that with the increase of TBOT concentration, the thickness of TiO2 layer in PS / TiO2 composite microspheres increases. This is because the concentration of TiO2 particles produced after hydrolysis increases with the increase of TBOT concentration. Under the action of electrostatic force, more TiO2 particles are coated on the surface of PS microspheres, thereby increasing the thickness of TiO2 layer.
[0060] Comparative experiment 3
[0061] Based on Example 1, only the amount of cerium nitrate in step 3 was changed to study its effect on the material of the present invention. Specifically, the amount of cerium nitrate and PS / TiO2 aqueous solution was 10g:1L and 25g:40L respectively; this experiment obtained a series of PS / TiO2 / CeO2 composite abrasives with different CeO2 layer thicknesses.
[0062] like Figure 5 The TEM images of PS / TiO2 / CeO2 composite abrasives prepared at three different cerium nitrate dosages of the present invention are shown. It can be seen from the figure that when the cerium nitrate dosage is 10g:1L, the number of CeO2 particles generated is very small, and finally only discretely distributed on the surface of the PS microspheres ( Figure 5 (a)). When the amount of cerium nitrate was 25g:1L, the number of CeO2 particles generated increased significantly, and a CeO2 layer was formed on the surface of the PS microspheres, but a complete coating layer was not formed ( Figure 5 (b)). When the amount of cerium nitrate was increased to 40 g / L, a complete CeO2 layer was formed ( Figure 5 As shown in (c), when the amount of cerium nitrate continued to increase, the CeO2 shell became thicker.
[0063] Comparative experiment 4
[0064] The PS / TiO2 / CeO2 composite abrasive was prepared by using Example 1, and the polishing was compared with CeO2 abrasive and PS / CeO2 composite abrasive. The specific method is as follows:
[0065] CeO2 abrasive, PS / CeO2 and PS / TiO2 / CeO2 composite abrasive were made into polishing liquid with the same concentration and used to polish KDP crystal.
[0066] Polishing conditions are as follows:
[0067] The polishing machine is a UNIPOL-1502 precision grinding and polishing machine, and the polishing pad is a polyurethane polishing pad.
[0068] The polishing pressure is 13.1 kPa, the polishing disc speed is 90 r / min, the polishing liquid flow rate is 0.1 L / min, and the polishing time is 10 min.
[0069] The microscopic morphology of the polished KDP crystal surface was observed using a Dimension Edge atomic force microscope (AFM) from Bruker, Germany. Figure 6 Shown are AFM images of the PS / TiO2 / CeO2 composite abrasive prepared in Example 1 of the present invention and CeO2 and PS / CeO2 abrasives after polishing KDP crystals.
[0070] After testing and analysis, the crystal surface roughness R a 1.12nm( Figure 6 (a)), material removal rate is 185nm / min; after polishing with PS / CeO2 composite abrasive, the crystal surface roughness R a 0.39nm( Figure 6 (b)), the material removal rate is 137nm / min; after polishing with PS / TiO2 / CeO2 composite abrasive, the crystal surface roughness R a 0.34nm( Figure 6 (c)), MRR is 176nm / min. Compared with CeO2 abrasive, PS / CeO2 composite abrasive significantly improves the surface finish of the crystal, but the material removal rate is reduced. The PS / TiO2 / CeO2 composite abrasive prepared by the present invention can not only reduce the surface roughness of the crystal, but also obtain a high material removal rate, thereby improving the polishing effect. This is because the elastic modulus of the inner core of the PS microsphere is about 3GPa, which is much lower than the elastic modulus of the CeO2 grains (200GPa). The compression elastic modulus of the PS / TiO2 / CeO2 composite abrasive prepared by the present invention is about 9GPa measured by the nanoindentation method, which greatly reduces the scratches on the surface of the KDP crystal. At the same time, the synergistic effect of TiO2 and CeO2 improves the polishing efficiency.
[0071] The above embodiments are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation methods. For those of ordinary skill in the art, other different forms of changes can be made based on the above description. And the obvious changes derived from this belong to the scope of protection of the present invention. Finally, it should be noted that the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
Claims
1. A method for preparing a double-layer core-shell structure PS / TiO2 / CeO2 nanocomposite abrasive, comprising the following steps: Step 1: Preparation of polystyrene (PS) microspheres: Styrene and methacryloyloxyethyl trimethylammonium chloride are added to a polyvinyl pyrrolidone aqueous solution, and 2,2-azobis(2-methylpropylimidazole) dihydrochloride is added thereto after heating to boiling to obtain a polystyrene emulsion, and the emulsion is dried and ground to obtain PS microspheres; Step 2: Preparation of PS / TiO2 composite microspheres: The PS microspheres prepared in step 1 are dispersed in anhydrous ethanol to prepare a PS ethanol solution, and ultrasonically dispersed uniformly; the pH value of the mixed solution is then adjusted to 6-9 with ammonia water, and heated; the ethanol solution of organic titanate is then added and stirred for reaction; after the reaction is completed, the product is centrifuged and repeatedly washed with deionized water and anhydrous ethanol; then dried and ground to obtain PS / TiO2 composite microspheres; Step 3: Preparation of PS / TiO2 / CeO2 composite abrasive: The PS / TiO2 composite microspheres prepared in step 2 are dispersed in deionized water to prepare a PS / TiO2 aqueous solution, and ultrasonically dispersed evenly; then, soluble cerium salt and hexamethylenetetramine are added; the reaction is stirred under heating conditions; after the reaction is completed, the final product is centrifuged and repeatedly washed with deionized water and anhydrous ethanol; finally, the PS / TiO2 / CeO2 composite abrasive is obtained by drying and grinding.
2. The method for preparing the double-layer core-shell structure PS / TiO2 / CeO2 nanocomposite abrasive according to claim 1, characterized in that: In step 1, the concentration of the polyvinyl pyrrolidone aqueous solution is 0.5g / L~6g / L; the dosage relationship of styrene and polyvinyl pyrrolidone aqueous solution is 45g~150g:1L; the dosage relationship of methacryloyloxyethyl trimethyl ammonium chloride and polyvinyl pyrrolidone aqueous solution is 0.5g~5.5g:1L; the dosage relationship of 2,2-azobis(2-methylpropylimidamide) dihydrochloride and polyvinyl pyrrolidone aqueous solution is 0.5g~2.5g:1L; in step 1, a constant temperature oil bath is used for heating at a temperature of 100~110°C, and the reaction is carried out for 5~8h after adding 2,2-azobis(2-methylpropylimidamide) dihydrochloride.
3. The method for preparing the double-layer core-shell structure PS / TiO2 / CeO2 nanocomposite abrasive according to claim 1, characterized in that: In step 2, the organic titanate is any one of tetrabutyl titanate, isopropyl titanate, and titanium isopropoxide, or a combination thereof.
4. The method for preparing the double-layer core-shell structure PS / TiO2 / CeO2 nanocomposite abrasive according to claim 1, characterized in that: In step 2, the concentration of the PS ethanol solution is 5 g / L to 30 g / L, and the concentration of the organic titanate ethanol solution is 10 g / L to 100 g / L; in step 2, a constant temperature oil bath is used for heating, the heating temperature is 70 to 90° C., and the reaction time is 2 to 4 hours.
5. The method for preparing the double-layer core-shell structure PS / TiO2 / CeO2 nanocomposite abrasive according to claim 1, characterized in that: In step 3, the soluble cerium salt is any one of cerium nitrate, cerium sulfate, cerium chloride or a combination thereof.
6. The method for preparing the double-layer core-shell structure PS / TiO2 / CeO2 nanocomposite abrasive according to claim 1, characterized in that: In step 3, the concentration of the PS / TiO2 aqueous solution is 2.5g / L~15g / L, the dosage of the soluble cerium salt and the PS / TiO2 aqueous solution is 20g-100g:1L; the molar ratio of the soluble cerium salt to hexamethylenetetramine is 1:5; in step 3, a constant temperature oil bath is used for heating, the heating temperature is 60~85°C, and the reaction time is 2~4h.
Citation Information
Patent Citations
CeO2 / TiO2 nanometer composite hollow sphere catalyst and preparation method thereof
CN104001491A
Preparation method for hollow microsphere SCR denitration catalyst
CN107159182A
Structural color paste capable of being coated and sprayed and preparation method thereof
CN113105769A
Polishing solution for KDP (potassium dihydrogen phosphate) crystal and efficient grinding and polishing process
CN115181498A
Preparation method of mesoporous cerium oxide coated polystyrene nano composite abrasive material under microwave condition
CN115449345A